Investment strategies of non-state pension funds: world experience - Suimenbayeva А.М.; Bekenova А.Б.; Aldabergen А.Е. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
This article examines the recent experience of the country and abroad to understand whether it satisfies the need for liquidity for pension provision in mandatory and voluntary fixed income schemes and how this is done. The goal of a well-designed pension system is to reduce poverty in old age and balance a person’s income throughout his life. Over the past thirty years, changing demographic trends have led to a shift from pay-as-you-go schemes, in which the obligation to pay retirement income is imposed on the State and employers, and defined contribution schemes to defined benefit occupational pension benefits. Switching to fixed income schemes can help people establish a closer link between pension contributions and benefits. However, balancing specific pre-retirement liquidity needs, access to savings, and tracking sufficient income after retirement is becoming an increasingly difficult task for individuals. The need to maintain this balance correctly is becoming increasingly acute, as the coverage of national social security systems is often expanded by increasing the number of unpaid workers with low incomes, more periods of unemployment and irregular wages. He also uses simple modeling to show the impact of providing access to retirement savings on income adequacy after retirement. Research shows that limited access to retirement savings under stress can help improve the overall well-being of these people. The purpose of this article is to determine the prospects for the development of NPFs as institutional investors in the country.